Eco-School Arab App A Proposed Digital Model to Enhance Sustainable Environmental Behavior Among Primary School Students in the Arab World (Al-Farooq Journal of Sciences, 2026)
Educational systems across the Arab world suffer from a significant gap between theoretical environmental awareness acquired through curricula and practical sustainable behavior reflected in students' daily actions both inside and outside school. This gap[1] is not limited to any single Arab country but represents a shared phenomenon attributed to multiple factors: absence of behavioral measurement tools, lack of interactive digital content, weak connection between knowledge and daily practice, in addition to limited digital infrastructure in many Arab schools.This research paper presents a proposed mobile application model named "Eco-School Arab" specifically designed for primary school students (ages 6-14). The application is based on gamification theory, which has proven effectiveness[5-6] in behavior modification and enhancing intrinsic motivation among children. The application operates on a simple concept: converting positive environmental behaviors into points and symbolic rewards, where students record their daily green behaviors (such as turning off lights when leaving the classroom, properly closing water taps, sorting waste into designated containers, bringing reusable water bottles instead of single-use plastic bottles) by scanning QR codes placed in appropriate locations within the classroom.The application features several technical characteristics that make it suitable for the Arab context, most notably:Offline functionality with later data synchronization.Simple, colorful user interface suitable for different ages.Flexible points system adjustable by teachers according to their class needs.Periodic reports sent to teachers and parents about student behavioral progress.Support for Modern Standard Arabic with possibility of adding local dialects.The research thoroughly examines the main challenges facing green education application in the Arab context[2-7-8], extracted from literature review and a specially designed field survey. These challenges include: weak internet infrastructure in rural and remote areas, limited availability of tablets or smartphones for students in some schools, weak technical knowledge among some teachers and older staff, absence of supportive policies from Ministries of Education, scarcity of environmental educational content specifically designed for the Arab world, and absence of standardized measurement tools for environmental behavior assessment.To address these challenges, the research proposes a set of practical solutions:Designing the application to work on any older smartphone running Android 8 or newer.Providing paper alternatives for schools without digital devices (printed behavior cards).A short teacher training program (2 hours) explaining application usage.Policy proposals encouraging Ministries of Education to adopt the model experimentally in 10 schools per country.Creating an open-source Arab platform for sharing local environmental content among Arab countries.The application's concept and feasibility were tested through an electronic survey distributed to 30 teachers from three Arab countries: Egypt, Jordan, and Tunisia. Results showed that 83.3% of teachers face difficulty converting theoretical environmental awareness into practical behavior among their students. Additionally, 86.7% supported the idea that a points-and-rewards-based application could significantly encourage students to adopt positive behaviors. Regarding challenges, 73.3% of teachers considered weak internet as the biggest challenge, followed by device shortage (56.7%), then weak technical knowledge among students (40%). Meanwhile, 76.7% supported QR code scanning as a behavior recording method.Based on these results, the research recommends:Arab Ministries of Education adopt this model experimentally in a limited number of schools (10-20 schools) for a full academic semester, with continuous outcome evaluation.Allocating a small budget ($5,000-10,000) per country to develop a local version of the application appropriate to local curriculum and cultural specificity.Establishing partnerships with local telecommunications companies to provide free or discounted internet packages for participating schools.Integrating environmental technology skills into pre-service and in-service teacher preparation programs.Creating an annual Arab award for the school most applying digital green education to motivate schools to innovate in this field.The paper concludes that the Eco-School Arab application represents a promising model that can contribute to bridging the awareness-behavior gap in Arab schools, particularly with appropriate political support and funding. It also opens the door for further technological innovations in Arab environmental education and can be expanded to include other behaviors such as health, nutrition, and road safety.
Keywords: Green Education – Mobile Application – Environmental Behavior – Educational Technology – Arab World – Gamification – Sustainable Development